Cuantificación de metabolitos secundarios de hojas y corteza de Calliandra angustifolia por métodos espectrofotométricos - Villalta Magallanes, Maria del Carmen (2025)
Objective: To quantify the secondary metabolites present in the leaves and bark of Calliandra angustifolia using spectrophotometric methods. Methodology: Leaves and bark of C. angustifolia were collected in Quistococha (3°49’7” S, 73°19’53” O) and were certified by the curator of the Amazonian Herbarium at UNAP. The samples were cut and dried at 40 °C for one week. Subsequently, they were ground into a fine powder, which was stored in amber jars. UV/Vis techniques were used for the quantification of total phenols, flavonoids, anthocyanins, and catechins. Alkaloids were analyzed with methanol using a Soxhlet extractor and bromocresol green. Saponins were measured using the Lieberman-Burchard reagent at 528 nm. Results: The bark of C. angustifolia had higher amounts of total phenols (23,900.07 mg/100 g) and flavonoids (19,281 mg/100 g) than the leaves (22,474.45 mg/100 g and 16,730 mg/100 g, respectively). Anthocyanins were slightly higher in the bark (15,441 mg/100 g) compared to the leaves (15,156 mg/100 g). Catechins were very low in both parts (0.004 mg/100 g in the bark and 0.003 mg/100 g in the leaves). Alkaloids were more abundant in the leaves (29.58 mg/100 g) than in the bark (27.62 mg/100 g). The bark also showed a higher concentration of saponins (271.38 mg/100 g) compared to the leaves (137.06 mg/100 g). Conclusion: C. angustifolia shows significant potential for the development of new drugs, especially in its bark, which contains higher concentrations of total phenols, flavonoids, and saponins, highlighting its importance in therapeutic research.